CD8+ T-cell immunity orchestrated by iNKT cells - Qin, Yingyu; Bao, Xueyang; Zheng, Mingzhu (Frontiers in Immunology, 2023)
CD8+T cells belonging to the adaptive immune system play key roles in defending against virus infections and cancers. Current CD8+T cell-based immunotherapy has emerged as a superior therapeutic avenue that can eradicate tumor cells and long-term prevention of their recurrence in hematologic malignancies. It is believed that an effective adaptive immune response critically relies on the helps of innate compartment. Invariant natural killer T (iNKT) cells are innate-like T lymphocytes that have been considered some of the first cells to respond infections and can secrete a large amount of diverse cytokines and chemokines to widely modulate innate and adaptive immune response. Like CD8+T cells, iNKT cells also play an important role in defense of intracellular pathogenic infections and cancers. In this review, we will discuss the CD8+T cell immunity contributed by iNKT cells, including iNKT cell mediated cross-priming, memory formation and discuss recent advances in our understanding of the mechanisms underlying memory CD8+T cell differentiation, as well as aging induced impairment of T cell immunity.